Cross-sectional study of determinants of undernutrition among children aged 6–36 months in Kabul, Afghanistan - Shahbaz Ahmad Zakki; Ijaz ul Haq; Noorullah Rahimi; Mehwish Fayaz; Mohammad Taqi Rezaee (BMJ Open)
Objectives The current study aimed to find the distribution and factors associated with undernutrition among children aged 6–36 months in Kabul.Design Cross-sectional study.Setting Public Ataturk Children’s Hospital, Kabul.Participants 385.Methods A structured questionnaire was used to collect data on sociodemographic conditions and anthropometry of children. Logistic regression was used to find determinants of undernutrition.Results The distribution of stunting, wasting and underweight was 38.7%, 11.9% and 30.6%, respectively. Among the children studied, 54% did not receive breast milk within the first hour of birth, 53.2% were not exclusively breastfed, 21% received complementary feeding before the age of 6 months, 22.1% lacked access to safe water and 44.7% did not practise hand washing with soap. The odds of stunting were lower (p<0.05) in girls (AOR 5.511, 95% CI 3.028 to 10.030), children of educated fathers (OR 0.288, 95% CI 0.106 to 0.782), those from nuclear families (OR 0.280, 95% CI 0.117 to 1.258), those exclusively breastfed (OR 0.499, 95% CI 0.222 to 1.51) and those practising good hygienic practices (OR 0.440, 95% CI 0.229 to 0.847). Boys had high odd of girls (OR 6.824, 95% CI 3.543 to 13.143) while children of educated fathers (OR 0.340, 95% CI 0.119 to 0.973), those receiving complementary food at 6 months (OR 0.368, 95% CI 0.148 to 1.393) and those practising good hygiene (OR 0.310, 95% CI 0.153 to 0.631) had lower odds (p<0.05) of being underweight. Boys (OR 3.702, 95% CI 1.537 to 8.916) had higher odds of being wasted, whereas children of educated mothers (OR 0.480, 95% CI 0.319 to 4.660), those from nuclear families (OR 0.356, 95% CI 0.113 to 1.117), those receiving early breast feeding (OR 0.435, 95% CI 0.210 to 1.341) and those practising hand washing (OR 0.290, 95% CI 0.112 to 0.750) had lower odds (p<0.05) of being wasted.Conclusion This study demonstrated the sex of the child, illiteracy of fathers, not practising hand washing and not observing hygiene, late initiation of breast milk, complementary feeding timings, and lack of proper exclusive breast feeding as contributing factors to the under-nutrition of the children in the study population.